Strategi Komunikasi Pemasaran Terpadu Orlenalycious dalam Meningkatkan Brand Awareness Sebagai Cake Brownies Premium Pada Masyarakat di Kota Denpasar - Wulandari, Putri Cening; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium; Vol 4 No 2 (2023): Jurnal Ilmu Komunikasi Vol 4 No 2 Tahun 2023, 2024)
Orlenalycious is a brand that was established in 2018. Orlenalycious focuses on cake brownie products. Business competition in the culinary field is a challenge for Orlenalycious to maintain its existence. So, implementing the right marketing communication strategy is very necessary. The purpose of this study is to explain the integrated marketing communication strategy used by Orlenalycious to increase Brand Awareness. Using descriptive qualitative research methods and determining informants with purposive sampling techniques. Data obtained through interviews and documentation. The results of this study show that the strategy used by Orlenalycious uses two concepts, namely the marketing mix consisting of 7P product, place, price, promotion, people, process, physical evidence and IMC elements which consist of 8 elements, namely Advertising, Sales Promotion, Interactive Marketing, Direct Marketing, Personal Selling, Public Relations, Events, Word of Mouth. Marketing communication strategies have important influence on increasing Brand Awareness for Orlenalycious, namely interactive marketing and advertising. Keywords :   Brand Awareness, Integrated Marketing Communication, Marketing Mix, Orlenalycious.